RNA-binding activity of PHGDH drives amyloid-beta production in a human brain organoid model of sporadic Alzheimer’s disease - Junchen Chen; Ming Xu; Yuan Liu; Fatemeh Hadi; Shuanghong Xue; Shu Chien; Sheng Zhong (Proceedings of the National Academy of Sciences, 2026)
Pathological progression in sporadic Alzheimer’s disease (sAD) initiates with an early rise in soluble amyloid-β (Aβ), preceding plaque formation and neurodegeneration. However, the molecular event triggering this initial accumulation remains unknown. We report that phosphoglycerate dehydrogenase (PHGDH), a consistent biomarker of prodromal sAD, drives Aβ production through a previously unrecognized RNA-binding function. Specifically, PHGDH binds the 3′UTR of EIF2AK1 mRNA, enabling the physical interaction between PHGDH and the EIF2AK1 protein. By facilitating the recruitment of EIF2AK1 to its substrate EIF2α, this complex drives EIF2α phosphorylation, thereby selectively promoting the translation of BACE1, the rate-limiting enzyme for Aβ generation. We demonstrate that PHGDH overexpression elevates BACE1 protein and intracellular Aβ in neurons and astrocytes across mouse models and human brain organoids, independent of its canonical enzymatic or transcriptional roles. Mechanistically, this process requires a specific RNA-binding surface within PHGDH and the EIF2AK1 3′UTR. These findings define a PHGDH–EIF2AK1–EIF2α–BACE1 axis as a key driver of the earliest amyloid pathology in sAD.